2017
DOI: 10.1371/journal.ppat.1006635
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus differentially activates mTORC1 and mTORC2 signaling to maximize late stage replication

Abstract: Influenza A virus usurps host signaling factors to regulate its replication. One example is mTOR, a cellular regulator of protein synthesis, growth and motility. While the role of mTORC1 in viral infection has been studied, the mechanisms that induce mTORC1 activation and the substrates regulated by mTORC1 during influenza virus infection have not been established. In addition, the role of mTORC2 during influenza virus infection remains unknown. Here we show that mTORC2 and PDPK1 differentially phosphorylate A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 89 publications
(129 reference statements)
3
78
0
Order By: Relevance
“…As reported earlier, Ras-PI3K signaling axis acts as a host-oriented mechanism for viral internalization [40]. Moreover, a recent study has shown that mTORC1 activation supports viral protein expression and replication specifically at later stages of IAV infection when the cell is under significant stress [15]. In the present study, we have also shown that the IAV infection activates N-Ras, which further phosphorylates Akt and activates the downstream mTOR signaling proteins.…”
Section: Discussionsupporting
confidence: 86%
“…As reported earlier, Ras-PI3K signaling axis acts as a host-oriented mechanism for viral internalization [40]. Moreover, a recent study has shown that mTORC1 activation supports viral protein expression and replication specifically at later stages of IAV infection when the cell is under significant stress [15]. In the present study, we have also shown that the IAV infection activates N-Ras, which further phosphorylates Akt and activates the downstream mTOR signaling proteins.…”
Section: Discussionsupporting
confidence: 86%
“…The viral hemagglutinin (HA) protein, along with virus replication, can upregulate PDPK1-mediated phosphorylation and activate AKT, which is required for induction of the mTORC1 signaling pathway by the influenza virus. On the other hand, influenza M2 protein is capable of down-regulation of the mTORC1 inhibitor REDD1, thereby enhancing the mTORC1 activation [69]. mTORC1 signaling, in turn, promotes c-Myc expression at the translational level [70].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…(Hall, 2008). The high ATP/AMP ratio promotes and activates mTORC1, which leads to the dissociation of eIF4E from 4E-BP, ultimately resulting in enhanced protein synthesis (Brett et al, 2014), to support virus replication (Kuss-Duerkop et al, 2017;McNulty et al, 2013;Stohr et al, 2016). Conversely, antiviral role of mTORC1 has been demonstrated in CHIKV where virus has evolved a mechanism to bypass mTORC1 inhibition via MNK1/eIF4E mediated translation (Joubert et al, 2015) (Fig.…”
Section: Role Of Mnk1 In Cell Survival During Viral Infectionmentioning
confidence: 99%
“…This global inhibition of cellular protein synthesis aids in immune evasion (Ersahin et al, 2015;Porta et al, 2014). For example, influenza virus (Kuss-Duerkop et al, 2017), vaccinia virus and cowpox virus (Soares et al, 2009) activate mTORC2-Akt signaling which play a critical role in survivalbility at late stage of viral infection. However, in a study, DENV polyprotein was found to suppress only host cell translation at the level of translation initiation whereas viral protein synthesis remained unaffected.…”
Section: Role Of Mnk1 In Cell Survival During Viral Infectionmentioning
confidence: 99%